Stock Return Drivers in the Indonesian Sharia Capital Market: Evidence from Jakarta Islamic Index - Bela Adi Tariya; Agus Saur Utomo; Ishak Ishak (SAFE-Network, 2026)
This study investigates the key drivers of stock returns-specifically profitability, leverage, B/M ratio and firm size within the Indonesian sharia capital market context. This research adopts a quantitative methodology and applies panel data regression analysis using Eviews 12. The study relies on secondary data collected from the official publications of the Indonesia Stock Exchange and Yahoo Finance. The sample includes 11 firms listed on the Jakarta Islamic Index during the 2021-2024 period, selected through a purposive sampling technique. Quarterly observations were used, yielding a total of 176 observation. The results reveal that profitability exerts a positive and statistically significant influence on sharia stock returns. Debt ratios and firm size were found to have no significant influence on sharia stocks returns. Meanwhile, the price-to-book ratio has a significant negative effect on the returns of sharia stocks. The study offers a new theoretical contribution demonstrating that profitability information is a highly relevant tool that also serves as a signal (good news/bad news) for sharia investors in making investment decisions. Conversely, that variables of leverage and firm size were found not to be primary determinants in predicting stock returns. Sharia investors tend to focus more on a company’s growth prospects than on its fundamental value. Furthermore, the low level of leverage indicates that the restrictions on interest-based debt in the Jakarta Islamic Index (JII) effectively reduce agency problems, so that changes in debt ratios are no longer a primary consideration in investment decisions.